Coupling of PARP1-mediated chromatin structural changes to transcriptional RNA polymerase II elongation and cotranscriptional splicing - Elena A. Matveeva; Qamar M. H. Al-Tinawi; Eric C. Rouchka; Yvonne N. Fondufe-Mittendorf (Epigenetics & Chromatin, 2019)
Abstract Background Recently, we showed that PARP1 is involved in cotranscriptional splicing, possibly by bridging chromatin to RNA and recruiting splicing factors. It also can influence alternative splicing decisions through the regulation of RNAPII elongation. In this study, we investigated the effect of PARP1-mediated chromatin changes on RNAPII movement, during transcription and alternative splicing. Results We show that RNAPII pauses at PARP1–chromatin structures within the gene body. Knockdown of PARP1 abolishes this RNAPII pausing, suggesting that PARP1 may regulate RNAPII elongation. Additionally, PARP1 alters nucleosome deposition and histone post-translational modifications at specific exon–intron boundaries, thereby affecting RNAPII movement. Lastly, genome-wide analyses confirmed that PARP1 influences changes in RNAPII elongation by either reducing or increasing the rate of RNAPII elongation depending on the chromatin context. Conclusions These studies suggest a context-specific effect of PARP1–chromatin binding on RNA polymerase movement and provide a platform to delineate PARP1’s role in RNA biogenesis and processing.